2015
DOI: 10.1002/stem.1993
|View full text |Cite
|
Sign up to set email alerts
|

YAP1 Regulates OCT4 Activity and SOX2 Expression to Facilitate Self-Renewal and Vascular Mimicry of Stem-Like Cells

Abstract: Non-small cell lung cancer (NSCLC) is highly correlated with smoking and has very low survival rates. Multiple studies have shown that stem-like cells contribute to the genesis and progression of NSCLC. Our results show that the transcriptional co-activator YAP1, which is the oncogenic component of the Hippo signaling pathway, is elevated in the stem-like cells from NSCLC and contributes to their self-renewal and ability to form angiogenic tubules. Inhibition of YAP1 by a small molecule or depletion of YAP1 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 73 publications
5
131
1
2
Order By: Relevance
“…The most commonly focused gene, YAP1, was found to be involved in tumour development and progression in different malignancies, including CRC. Although increased level of the YAP1 protein (assessed by WB) was found in most studies [83,[88][89][90][91] suggesting its oncogenic role, the under-expression was also observed in breast [92] and colorectal cancer [79]. The study of Barry et al showed decreased expression of YAP1 in high grade tumours and stage IV [79].…”
Section: The Role Of Hippo Pathway In Colorectal Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…The most commonly focused gene, YAP1, was found to be involved in tumour development and progression in different malignancies, including CRC. Although increased level of the YAP1 protein (assessed by WB) was found in most studies [83,[88][89][90][91] suggesting its oncogenic role, the under-expression was also observed in breast [92] and colorectal cancer [79]. The study of Barry et al showed decreased expression of YAP1 in high grade tumours and stage IV [79].…”
Section: The Role Of Hippo Pathway In Colorectal Cancermentioning
confidence: 97%
“…Mouse KO: various cancer types developed [141] TSG: downregulation in CRC [142] TAZ Mutations in Barth syndrome [143] OG: overexpression in breast cancer [144], HCC [145] OG: overexpression in CRC [85] YAP1 OG: overexpression in NSCLC [88], prostate [90], breast [91], gallbladder cancer [146] and glioma [89] TSG: decreased expression in breast cancer [92] OG: overexpression in CRC [83], in CRC cases resistant to cetuximab [102] TSG: underexpression in CRC [79] AML -acute myeloid leukaemia; CCL -cancer cell line(s); HCC -hepatocellular carcinoma; KO -knock out; LOH -loss of heterozygosity; NSCLC -non-small cell lung cancer; OG -oncogene; TSG -tumour suppressor gene epinephrine or glucagon repress YAP1/TAZ activity [45,46]. YAP1 could also be regulated by matrix stiffness independently from LATS1/2 phosphorylation.…”
Section: Mob1 Mob1mentioning
confidence: 99%
“…Its deregulation is frequently observed in many types of malignancies, suggesting that alterations of this signaling are connected with cancer progression and patient survival (7)(8)(9)21,33,34). The core components of this pathway include MST1/2, SAV1, LATS1/2 and MOB1 proteins (10,12,15).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Decreased expression of LATS1 gene and protein was observed in breast (16), colorectal (17) and non-small cell lung cancers (18), whereas lower MST2 mRNA and protein levels were reported in hepatocellular carcinoma (19) and malignant mesothelioma (20). Furthermore, the overexpression of YAP1 protein was observed in many cancer types, including lung (21), prostate (22), breast (23), and gallbladder cancers (24) and glioma (25). Since to date no quantitative analyses of the expression of the Hippo pathway effector, YAP1, and its key components, MST2 and LATS1 kinases, have been assessed in ccRCC, we decided to compare their mRNA and protein levels in tumor and normal kidney tissues, and in metastases of ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…We and other groups have demonstrated that A549 cells can be used to identify signaling molecules which acquire lung CSCs by an Aldefluor assay (Hirata et al, 2014;Bora-Singhal et al, 2015;Oh et al, 2015). To examine the effect of NNK on the size of the lung CSCs, we performed an Aldefluor assay in human lung cancer cell line A549.…”
Section: Nnk Increases the Proportion Of Aldh-positive Cells In A549mentioning
confidence: 99%